Pengelolaan Kewirausahaan Sekolah Bagi Kepala Sekolah Dasar Negeri - Unifah Rosyidi; Neti Karnati; Rugaiyah Rugaiyah (Program Studi Manajemen Pendidikan, 2022)
Elementary school administration is an activity to support the success of the quality of education in elementary schools. The scope of school administration activities includes the management of official letters and school archives. The management of official letters and archives in elementary schools is carried out by the principal assisted by a school operator. Their ability to manage official letters and school archives is still very lacking. Efforts to improve the capacity of principals and elementary school administration personnel can be given training on the management of official letters and school archives. The object (target audience) of the training activity was 25 heads of elementary schools in Pulo Gadung sub-district. The partners involved are the Tribe of the Education Office Region I of the East Jakarta Administration City. The training has been carried out for a day on Monday, August 15, 2022 via virtual with zoom cloud metting. The training materials consist of: entrepreneurship and entrepreneurship education in schools; the role of the principal in entrepreneurship; and primary school entrepreneurship management. The three materials were delivered by 3 lecturers of the Education Management study program FIP UNJ with lectures, questions and answers and assignments. The results of the training were very satisfying for the participants and the organizing committee, because all the material had been delivered well and was very useful for all training participants.